2018
DOI: 10.1016/s2095-3119(17)61853-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis-related protein genes involved in race-specific all-stage resistance and non-race specific high-temperature adult-plant resistance to Puccinia striiformis f. sp. tritici in wheat

Abstract: Pathogenesis-related protein genes involved in race-specific allstage resistance and non-race specific high-temperature adultplant resistance to Puccinia striiformis f. sp. tritici in wheat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Furthermore, we found that bracts may be an important component of the L. chinense defense system to protect other floral tissues because most of the bract-specific hub genes were related to plant defense, such as PR, LecRLK, and LRR-RLK. Previous studies have shown that PR, LecRLK, and LRR-RLK play roles in plant immunity and pathogen defense (Parrott et al, 2016;Wang and Bouwmeester, 2017;Farrakh et al, 2018). These findings indicate that tissue-specific genes play a significant role in maintaining tissue characteristics in L. chinense.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, we found that bracts may be an important component of the L. chinense defense system to protect other floral tissues because most of the bract-specific hub genes were related to plant defense, such as PR, LecRLK, and LRR-RLK. Previous studies have shown that PR, LecRLK, and LRR-RLK play roles in plant immunity and pathogen defense (Parrott et al, 2016;Wang and Bouwmeester, 2017;Farrakh et al, 2018). These findings indicate that tissue-specific genes play a significant role in maintaining tissue characteristics in L. chinense.…”
Section: Discussionmentioning
confidence: 71%
“…For instance in an earlier study, a reduction in photosynthesis was shown to enhance stripe rust resistance due to the interaction of Yr36 , encoding for wheat kinase STARTI ( WKSI ) with Psbo (a member of photosystem II) 69 without having any adverse effect on yield. Similarly, in another study, several genes encoding PR (pathogenesis-related) proteins, involved in a number of defense responses were shown to get induced in response to stripe rust infection in a number of wheat lines carrying different genes for ASR ( YrTr1, Yr76, Yrsp, Yrexp2 ) and HTAP ( Yr5, Yr59, Yr62 and Yr7b ) 70 . A number of downstream genes, apparently similar to the CGs identified in the present study and involved in processes mentioned above were also identified in a transcriptome study conducted using a pair of introgression lines, which differed for Yr5 52 .…”
Section: Discussionmentioning
confidence: 74%
“…On the basis of the similarity of their amino acid sequences, structures, serological relationships, and biological activities, the PRs have been grouped into 17 families ( Kaur et al, 2017 ). These PRs have diverse functions, contributing to cell wall rigidification, signal transduction, and antimicrobial activities, and they are mainly expressed in plants as chitinases, glucanases, and thaumatin-like proteins ( Farrakh et al, 2018 ). Many PRs are distributed in plant cell gaps and vacuoles, and their distribution is related to their isoelectric point and the exposure to stress ( Jo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%